Mentoring Arabic Writing Skills through the Mubasyir Method - Supriyadi, Moh. (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2025)
The mastery of Arabic writing skills remains a major challenge for Muslim youth, particularly in rural areas such as Pesanggar Village, Pamekasan, where Arabic learning is often limited to reading and memorization activities. Most learners can recognize and read Arabic words but struggle to express ideas coherently in written form. This mentoring program was designed to address this issue by implementing the Mubasyir Method, a direct and communicative approach emphasizing active practice, immediate feedback, and contextual learning. The main objective was to enhance participants’ ability to produce structured Arabic sentences and paragraphs while improving their confidence and motivation in writing. The study employed a qualitative-descriptive method supported by pre-test and post-test assessments, participant observations, and peer evaluations. Fifteen adolescents aged 13–18 participated in an eight-week mentoring program facilitated by Arabic instructors. The results demonstrated a 27% increase in overall writing performance, particularly in grammatical accuracy, sentence construction, and vocabulary use. Participants also showed remarkable improvement in writing fluency and self-expression, reflecting the motivational strength of interactive learning. Beyond linguistic gains, the program fostered a positive learning attitude, transforming students’ perceptions of Arabic writing from difficult to enjoyable. This study contributes to the growing body of literature on Arabic pedagogy by illustrating that the Mubasyir Method can serve as an effective framework for developing communicative and expressive writing competence in nonformal and rural educational contexts